2016
DOI: 10.1111/jfpp.13103
|View full text |Cite
|
Sign up to set email alerts
|

The Substance Basis Research of Stir-Baking to Dark Brown Could Enhance the Promoting Effects of Areca Nut on Gastrointestinal Motility

Abstract: The promoting effects of areca nut (AN) and charred areca nut (CAN) on gastrointestinal motility were compared. The HPLC analysis was used to compare the constituents in AN and CAN and the new produced constituents in CAN were isolated and identified. Then the promoting effects of the identified constituents on gastrointestinal motility were investigated in vivo. In the results, CAN showed stronger promoting effect on gastrointestinal motility than that of AN (P < 0.05) in vivo and in vitro. Three new constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It has been reported that MR begins with a condensation between carbonyl and amino groups. Subsequently, a series of reactions take place, such as Amadori rearrangement, enolization, Strecker degradation, aldol condensation and aldehyde-amide polymerization, leading to the formation of melanoidins and fragrant flavors [3,15]. In the present study, the contents of sugars and amino acids were determined in the raw and steamed PN root, and the results indicated that the heating-induced reduction in reducing sugars and amino acids may be due to the MR.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It has been reported that MR begins with a condensation between carbonyl and amino groups. Subsequently, a series of reactions take place, such as Amadori rearrangement, enolization, Strecker degradation, aldol condensation and aldehyde-amide polymerization, leading to the formation of melanoidins and fragrant flavors [3,15]. In the present study, the contents of sugars and amino acids were determined in the raw and steamed PN root, and the results indicated that the heating-induced reduction in reducing sugars and amino acids may be due to the MR.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies have reported that 5-HMF was the intermediate products of MR and it formed from dehydration and degradation of carbohydrates in MR [14,15]. The 5-HMF was often generated in processed Chinese material medica and it usually be regarded as an indicator of the degree of MR [16].…”
Section: Discussionmentioning
confidence: 99%
“…MTL, a polypeptide secreted by Mo cells, induces strong gastrointestinal motility. By contrast, VIP, released from the inhibitory vasoactive intestinal peptidergic fibers, leads to inhibition of gastric acid secretion and relaxation of the gastrointestinal tract25262728. Thus, increasing MTL and decreasing VIP could promote gastrointestinal motility.…”
Section: Discussionmentioning
confidence: 99%
“…Further comparisons found that Charred Semen Arecae had a more significant effect on gastrointestinal motility than areca nut, possibly due to the Maillard reaction products. [ 143 ]. Besides this, arecoline can promote the amplitude of smooth muscle contraction of the isolated small intestine in rabbits [ 144 ].…”
Section: Functional Effects Of Areca Nut Componentsmentioning
confidence: 99%